Results of the sentinel surveillance project, 2006: challenges for the control of congenital syphilis in Brazil - Szwarcwald, Célia L; Barbosa Junior, Aristides; Miranda, Angélica E; Paz, Leidijany C (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Objective: estimating HIV and syphilis prevalence rates among parturient women and coverage of HIV and syphilis testing during pregnancy by means of registered information in prenatal and hospital records. Methods: the sampling was probabilistic in two selection stages. In the first one, 150 hospitals were selected, stratified by population size of the municipality. In each health establishment, 100-120 parturient were randomly selected. Coverage of syphilis testing was estimated among parturient women who took two syphilis tests during prenatal care and one test at delivery. Syphilis prevalence rate was estimated among parturient women tested at the delivery. Results: only 14.1% of the women followed the recommendations of two syphilis tests during pregnancy and one at the delivery. The percentage of pregnant women with at least one syphilis test registered in the prenatal record was 75.1% but only 16.9% showed two test results. Among pregnant women that were tested at delivery, 1.1% had positive results. Among women that were tested during prenatal care and were negative, 0.4% got positive in the second test. Among women who did not have prenatal care and were tested at delivery, 1.8% had positive results. Conclusion: the low coverage of the second syphilis test indicates that the Ministry of Health recommendations are not being obeyed in the routine of health services. The findings depicted indicate the need of the second syphilis test during pregnancy for the adequate vertical transmission control.